2008
DOI: 10.1111/j.1747-0285.2008.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

A Small Subset of Signal Peptidase Residues are Perturbed by Signal Peptide Binding

Abstract: Perturbations of the chemical shifts of a small subset of residues in the catalytically active domain of Escherichia coli signal peptidase I (SPase I) upon binding signal peptide suggest the contact surface on the enzyme for the substrate. SPase I, an integral membrane protein, is vital to preprotein transport in prokaryotic and eukaryotic secretory systems; it binds and proteolyses the N-terminal signal peptide of the preprotein, permitting folding and localization of the mature protein. Employing isotopicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Three lysines were added at each terminus to enhance solubility of the peptide. Addition of these lysines does not perturb the ability of this peptide to interact with the signal peptidase 79. KAP25 stimulates SecA ATPase activity, indicating that it binds to SecA in a functionally-relevant manner.…”
Section: Methodsmentioning
confidence: 97%
“…Three lysines were added at each terminus to enhance solubility of the peptide. Addition of these lysines does not perturb the ability of this peptide to interact with the signal peptidase 79. KAP25 stimulates SecA ATPase activity, indicating that it binds to SecA in a functionally-relevant manner.…”
Section: Methodsmentioning
confidence: 97%
“…Furthermore, it is consistent with our previous work showing the interaction of this same peptide with SecA, 15 another component of the Sec-dependent transport pathway, and a comparable peptide with SPase I Δ2-75. 10 Moreover, we found that the enzyme slowly cleaves the KAP25 signal peptide with about 7, 19 and 27% cleavage observed at 24, 36 and 48 hours of incubation, respectively (data not shown). This slow extent of cleavage is consistent with previous studies that report a decrease in preprotein digestion by SPase I and the soluble form in the absence of Triton X-100 and for a small peptide relative to the preprotein.…”
Section: Resultsmentioning
confidence: 87%
“…To circumvent this issue, we previously reported that the addition of three lysine residues to each termini is a good strategy to design highly soluble signal peptides, 10,15 which can be studied by NMR or other biophysical techniques. In this study, we used a comparable approach to examine the E. Coli alkaline phosphatase signal peptide (KAP25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a complex system plays an essential role in many biological activities such as cell -cell communication [3,4], receptor-mediated signal transduction [5,6], enzyme catalysis [7,8], selective transport of metabolites [9,10], and pharmacological actions [11,12]. Thus, membrane protein studies are important for understanding their functions in different biological processes.…”
Section: Introductionmentioning
confidence: 99%